2013
DOI: 10.1016/j.ejvs.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific Rehearsal Prior to EVAR: A Pilot Study

Abstract: PsR for EVAR permits creation of realistic case studies. Subjective evaluation indicates that it may influence optimal C-arm angles and be valuable to prepare the entire team. A randomised controlled trial (RCT) is planned to evaluate how this technology may influence technical and team performance, ultimately leading to improved patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 22 publications
0
57
0
Order By: Relevance
“…Both face and content validity were supported by experts in the studies by Desender et al and Hislop et al 13,14 Face validity is the degree to which the simulator resembles a real life situation and content validity is the degree to which the domain being measured is measured by the simulator. 6 In the patient specific procedure rehearsals conducted by Willaert et al and Desender et al, 10,13 inexperienced trainees subjectively felt that simulation helped them to familiarize themselves with the procedure. In both studies, the simulator was also proven to be able to predict the fluoroscopy angle significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both face and content validity were supported by experts in the studies by Desender et al and Hislop et al 13,14 Face validity is the degree to which the simulator resembles a real life situation and content validity is the degree to which the domain being measured is measured by the simulator. 6 In the patient specific procedure rehearsals conducted by Willaert et al and Desender et al, 10,13 inexperienced trainees subjectively felt that simulation helped them to familiarize themselves with the procedure. In both studies, the simulator was also proven to be able to predict the fluoroscopy angle significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Desender et al performed a prospective, multicenter study of endovascular aortic aneurysm repair (EVAR) on nine patients with infrarenal abdominal aortic aneurysm. 13 Three dimensional reconstruction was also performed with SimbionixPROcedure and PsPR was performed 24 hours before EVAR. Technical metrics were recorded during both procedures.…”
mentioning
confidence: 99%
“…These include full body mannequins such as the VIST ® -Lab (Mentice AB, Sweden) which consists of simulated instruments, and performance metrics such as contrast volume and fluoroscopy time 3. Other simulators provide pre-procedure rehearsal and simulated training of different procedures with added haptic feedback 4. Thus far quantitative information on operator–tool interactions, tool–tissue interactions, and skill-related behaviour patterns is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Two relevant studies were excluded from our review based on study design 28 29. Willaert et al 28 found that patient-specific rehearsal prior to operation may be helpful in preoperative preparation and operative performance, and Desender et al 29 found that patient-specific rehearsal prior to endovascular aortic aneurysm repair to be feasible and to have face validity, but neither study design included a formal no JiT training control group.…”
Section: Resultsmentioning
confidence: 99%